2020
DOI: 10.1002/etc.4807
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Transfer Reaction Free Energy as a Predictor of Abiotic Nitroaromatic Reduction Rate Constants: A Comprehensive Analysis

Abstract: A linear free energy model is presented that predicts the second‐order rate constant for the abiotic reduction of nitroaromatic compounds (NACs). Previously presented models use the one‐electron reduction potential EH1(ArNO2) of the NAC reaction ArNO2+e−→ArNO2•−. If EH1(ArNO2) is not available, it has been proposed that EH1(ArNO2) be computed directly or estimated from the gas‐phase electron affinity (EA). The model proposed uses the Gibbs free energy of the hydrogen atom transfer (HAT) reaction ArNO2+H•→ArNOO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The HAT energy, which corresponds to the transfer of a single hydrogen atom (i.e., 1e – + 1H + ), is described in eq for NAC/MC reduction where MCH • is the radical that results from the hydrogen atom (H • ) transfer to an MC molecule. While the aqueous-phase one-electron reduction potential ( E H 1 ) has been utilized previously as the NAC/MC energy descriptor in reduction kinetics LFERs, ,,,, our more recent studies have shown that calculated HAT energies work as well, , and in some cases better, than the calculated E H 1 values.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…The HAT energy, which corresponds to the transfer of a single hydrogen atom (i.e., 1e – + 1H + ), is described in eq for NAC/MC reduction where MCH • is the radical that results from the hydrogen atom (H • ) transfer to an MC molecule. While the aqueous-phase one-electron reduction potential ( E H 1 ) has been utilized previously as the NAC/MC energy descriptor in reduction kinetics LFERs, ,,,, our more recent studies have shown that calculated HAT energies work as well, , and in some cases better, than the calculated E H 1 values.…”
Section: Methodsmentioning
confidence: 95%
“…where MCH • is the radical that results from the hydrogen atom (H • ) transfer to an MC molecule. While the aqueousphase one-electron reduction potential (E H 1 ) has been utilized previously as the NAC/MC energy descriptor in reduction kinetics LFERs, 3,11,14,15,30−32 our more recent studies have shown that calculated HAT energies work as well, 13,33 and in some cases better, 20 than the calculated E H 1 values. The computed standard state free energies of formation in eq 7 were obtained using the DFT functional M06-2X and 6-311++G(2d,2p) basis set.…”
Section: T H Imentioning
confidence: 94%
See 2 more Smart Citations
“…Given that ET and HAT energies accurately describe the reduction rate constants of mono-nitro NACs and that they can be computed from molecular structures without experimental data, the suitability of both energies as thermodynamic descriptors for predicting MC reduction rate constants was evaluated. Surprisingly, ET and HAT energies and experimental second-order rate constants of MCs are scarce or nonexistent in the literature, particularly for NTO and DNP.…”
Section: Introductionmentioning
confidence: 99%